Optimering av tappningsförfarandet på LD - Persson, Amanda (2011)
The production of raw steel at SSAB EMEA in Luleå is carried out in basic oxygen steelmaking furnaces (BOF), where dissolved carbon in pig iron is reduced to a level less than 2 % through the reaction with oxygen. Simultaneously, a slag phase is formed consisting of oxidized impurities from the metal phase and slag formers. To prevent slag from escaping to the steel ladle in the end of the tapping performance, SSAB EMEA in Luleå uses a slag stopper system consisting of mainly two units; a slag detection device followed by a unit that mechanically is forcing the slag back into the furnace. The latter device utilizes a high pressure of inert nitrogen gas coming from a nozzle that is positioned in front of the tap hole. The slag stopper system was introduced in spring and autumn of 2010 in which the system enables a better control of carried-over slag. To allow for an optimized tapping performance with a low amount of carried-over slag combined with a high iron exchange, metallurgical studies focused on the tapping action were performed during spring 2011. The aim of this thesis was to find which parameters that have the largest influence on carried-over slag by creating a multivariate statistically model. Since no measurements on carried-over slag are normally performed in daily practice, methods to estimate this parameter where searched for in the literature. To get an estimation of carried-over slag, slag samples and measurements on the slag thickness in the ladle were collected. Estimated carried-over slag and iron exchange were considered together with process data when creating statistical models in the computer program SIMCA-P+ 12.0 (SIMCA). The purpose was to enable an evaluation of the correlations existing among process parameters and the outcome of the tapping performance. When estimated values for carried-over slag were evaluated against a number representing how much slag that had been detected during tapping (SMI), statistical models with the strongest correlations were formed. From these, it was ...